2013
DOI: 10.3184/003685013x13592844053451
|View full text |Cite
|
Sign up to set email alerts
|

Optical Trapping of Nanoparticles by Ultrashort Laser Pulses

Abstract: Optical trapping with continuous-wave lasers has been a fascinating field in the optical manipulation. It has become a powerful tool for manipulating micrometer-sized objects, and has been widely applied in physics, chemistry, biology, material, and colloidal science. Replacing the continuous-wave- with pulsed-mode laser in optical trapping has already revealed some novel phenomena, including the stable trap, modifiable trapping positions, and controllable directional optical ejections of particles in nanomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 115 publications
(247 reference statements)
4
58
0
Order By: Relevance
“…In our earlier reports, theoretically, we have shown that directional ejections of the nanoparticles can occur as a result of dominating repulsive−over attractive-forces in the directions perpendicular to the polarization vector. 27,30 The reasonable questions arise; e.g., how are the nanoparticles ejected from the trapping site and what parameters can control such directional ejections? On the basis of electromagnetic formulations, a multitude of parameters, such as the repetition rate and pulse duration of laser pulses, as well as numerical aperture of objective lens can greatly affect the repulsive and attractive forces.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier reports, theoretically, we have shown that directional ejections of the nanoparticles can occur as a result of dominating repulsive−over attractive-forces in the directions perpendicular to the polarization vector. 27,30 The reasonable questions arise; e.g., how are the nanoparticles ejected from the trapping site and what parameters can control such directional ejections? On the basis of electromagnetic formulations, a multitude of parameters, such as the repetition rate and pulse duration of laser pulses, as well as numerical aperture of objective lens can greatly affect the repulsive and attractive forces.…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that the directional ejections occur only when the number of nanoparticles confined in the trapping site exceeds a definite threshold. Considering electromagnetic formulation and its numerical estimation, however, trapping and ejection are always symmetrical with respect to the polarization of the incident trapping pulses [25]. Thus, we have to ascribe the alternatively switched ejection behavior to material property.…”
Section: Trapping and Ejection Dynamics By Femtosecond Laser Pulsesmentioning
confidence: 99%
“…It should be noted also that x-, y-and z-polarizations of the trapping laser are no more independent after being focused tightly with an objective lens of high numerical aperture, where z axis corresponds to the propagating direction of the tapping laser. Considering these forces, we formulated electromagnetic theorem of forces on the polystyrene nanoparticles at the focal point [25]. It should be pointed out that laser trapping by femtosecond pulses is based on repetitive irradiation mode.…”
Section: Trapping and Ejection Dynamics By Femtosecond Laser Pulsesmentioning
confidence: 99%
“…Since its first conception and realization, optical trapping of microscopic objects in a solution with a highly focused laser beam has emerged as a common practice to manipulate particles of micrometer size [1], and has found applications in various disciplines ranging from physics [2][3][4][5] and chemistry [6] to biology [7][8][9][10]. The optical manipulation of nanometer-sized particles with a great efficiency and stability nevertheless remains a challenge, and is demonstrated almost exclusively on particles made of noble metals or semiconductors [11][12][13].…”
Section: Introductionmentioning
confidence: 99%